Alterations of Serum Calcium, Phosphorus and AlkalinePhosphatase in Postmenopausal Women (Tikrit Journal of Pharmaceutical Sciences, 2023)
In the present study 3 biochemical parameters ( Calciun1i Phosphorus and Alkaline phosphatase) has been measured in blood of 111 apparently healthy volunteers women, including 41 apparently healthy premenopausal women aged between ( 21- 42 ) years as a .control group and 70 apparently healthy postmenopausal women ( tbe menopause occur normally ) aged between ( 50- 69 ) years which divided into two age groups. From the results it is found that there were a significant difference of serum calcium, phosphorus and alkaline phosphatase between postmenopausal women group and control group also the current study showed that lhe serum calcium and phosphorus declines with age with in postmenopausal women group. while the mean value of alkaline phosphatase activity showed a significant increase with increasing age in postrnenopausal women group.